2017
DOI: 10.2147/ott.s124417
|View full text |Cite
|
Sign up to set email alerts
|

RASSF1A promoter methylation is associated with increased risk of thyroid cancer: a meta-analysis

Abstract: ObjectivePrevious studies have reported that Ras-associated domain family 1A (RASSF1A), the most commonly silenced tumor suppressor via promoter methylation, played vital roles in the development of carcinogenesis. The purpose of this meta-analysis was to determine whether RASSF1A promoter methylation increased the risk of thyroid cancer.MethodsPubMed, Embase, ISI Web of Knowledge, and Chinese National Knowledge Infrastructure databases were searched to obtain eligible studies. The pooled odds ratios (ORs) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…We identified that the sensitivity value of methylated FAM19A4 and PLR value of methylated RASSF1A , FHIT , MGMT , and p16 are relatively high, suggesting that they are comprehensive parameters for the screening test [ 61 ]. In addition, methylated RASSF1A and p16 genes are reported to be promising driving molecules in many cancers under the concept of precision medicine [ 9 , 62 , 63 , 64 , 65 , 66 , 67 ]. In addition, the methylation of FAM19A4 , FHIT , and MGMT were reported to play important roles in the occurrence and deterioration of lung cancer [ 68 , 69 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…We identified that the sensitivity value of methylated FAM19A4 and PLR value of methylated RASSF1A , FHIT , MGMT , and p16 are relatively high, suggesting that they are comprehensive parameters for the screening test [ 61 ]. In addition, methylated RASSF1A and p16 genes are reported to be promising driving molecules in many cancers under the concept of precision medicine [ 9 , 62 , 63 , 64 , 65 , 66 , 67 ]. In addition, the methylation of FAM19A4 , FHIT , and MGMT were reported to play important roles in the occurrence and deterioration of lung cancer [ 68 , 69 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its increased expression can mainly make tumor cells resistant to cisplatin (24). The aberrant methylation of RASSF1A gene serves an important role in the occurrence and development of various tumors, including bladder cancer and thyroid cancer (25,26), and is associated with drug resistance and tumor prognosis (27,28). The purpose of the present study was to detect the expression of drug resistance genes and aberrant methylation of RASSF1A in different types of ovarian tissues and to investigate their role in the primary resistance of ovarian cancer.…”
Section: Discussionmentioning
confidence: 98%
“…The hypermethylation of TSG promoter suppresses genes expression by inhibiting transcription, thereby affecting cell signaling pathways. Two previous meta-analyses demonstrated the association between RASSF1A promoter methylation and PTC risk [ 31 , 41 ]. In the current report, a comprehensive review was carried out to determine the relationship between thyroid cancer susceptibility and gene methylation.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, RASSF1 promoter inactivation has been detected in more than 30% of thyroid tumors, representing the most and frequent event in thyroid cancers [ 72 , 73 ]; however, in some reports, no significant correlation between RASSF1 methylation and thyroid cancer risk was detected [ 68 , 74 – 78 ]. In two prior meta-analyses, researchers only examined the association between RASSF1 promoter methylation and PTC risk [ 31 , 41 ]. Although the results of these prior meta-analyses demonstrated that the frequency of RASSF1 promoter methylation was significantly associated with increased risk of thyroid cancer, our study showed that the influence of RASSF1 promoter methylation was lower than those of CDH1 and SLC5A8 promoter methylation.…”
Section: Discussionmentioning
confidence: 99%